Domestic violence in Pakistan: the legal construction of 'bad' and 'mad' women - Kamal, Daanika (Clarendon studies in criminology, 2025)
"This book is based on my doctoral thesis, made possible by the funding I received from Queen Mary University of London through the Principal's Research Studentship, and the academic support of a supervisory dream team. Ruth Fletcher has been a phenomenal mentor, and I am hugely grateful for her ongoing dedication, curiosity and guidance. Leila Ullrich and Jeffrey Kennedy have continued to provide invaluable encouragement from near and far, keeping me optimistic and motivated every step of the way. I am equally grateful to my PhD examiners, Vanessa Munro and Penny Green, for deeply and thoroughly engaging with this work, and for providing feedback that has significantly strengthened many parts of it"-- Provided by publisher